Impact of HVDC link and electric vehicle on multi-area power system using MOA optimized I-TD2N controller - Tirumalasetty Chiranjeevi; B.S.S. Ganesh Pardhu; Naladi Ram Babu; Sumana Das; Kareem M. AboRas; Wulfran Fendzi Mbasso; Pamarthi Sunitha; Adireddy Ramesh; Pradeep Jangir; Mohammad Khishe (Results in Engineering)
This article examines the effects of HVDC link and Electric Vehicles (EVs) on multi-area Power Systems (PS). The suggested system features with EVs, HVDC link a thermal unit. A novel controller, termed the integral minus tilt double derivative (I-TD2N), has been developed as an auxiliary controller. The controller settings were effectively optimized through the application of the Mayfly optimization algorithm (MOA). Comparing the dynamic responses of the system with PID, TID, and I-TD2N controllers, it was found that I-TD2N controller offered best performance. Further, a comparative study was made to deliberate the best performance index over ISE, ITSE, IAE and ITAE. Studies suggest that ISE exhibits faster convergence over others. The study with incorporating of HVDC link showed that HVDC links enhance the system's dynamic performance. Furthermore, integrating HVDC link and EVs significantly improved dynamic responses. Additionally, a sensitivity analysis was carried out to evaluate the suggested I-TD2N controller's resilience under various loading scenarios.